Perspectives of Ag(10%):InP/ZnS MPA nanoparticles application in the treatment of yeast keratomycosis - V.O. Ponomarev; V.N. Kazaikin; S.V. Dezhurov; V.L. Timofeev (Офтальмохирургия)
Relevance. Resistant fungal keratitis (keratomycosis) is a big current problem in ophthalmology. The limited arsenal of drugs and the low efficiency of surgical treatment often leads to extremely low anatomical and functional results. One of the alternative approaches to the management of fungal keratitis can be the use of nanoparticles, in monotherapy, or as a catalyst for a more effective effect of a native drug. Quantum dots (QDs) act as nanoparticles. Under the action of light in the visible region of the spectrum, QDs are capable of participating in redox reactions and the simulated formation of reactive oxygen species (ROS) by changing the electronic interactions with the surrounding atoms. Purpose. Synthesis of QDs potentially active against fungal microflora, study of the ability of this type of QDs and analogues to produce ROS and analysis of their fungicidal activity against yeast microflora in vitro. Material and methods. The study determined the effectiveness of the QDs solution in suppressing the growth of colonies of resistant species of fungi of the genus Candida spp (C. albicans, C. glabrata, C. tropicalis, C. Parapsilosis) in vitro. QDs Ag(10%):InP/ZnS MPA were used in the form of a native solution (10%) and at a dilution of 1:100 (0.1%). Results. It was possible to reveal the complete suppression of the visible growth of Candida spp. in the area treated with QDs, regardless of concentration. The diameter of the growth inhibition zone (GIZ) in all cases exceeded 24 mm, which corresponded to a high degree of sensitivity. Conclusion. The synthesized Ag(10%):InP/ZnS MPA QDs showed high anti-infective activity against the resistant yeast microbiota Candida spp. in laboratory conditions, playing one of the primary roles in the course of keratomycosis. It is necessary to consider QDs Ag(10%):InP/ZnS MPA as one of the alternative/additional agents for the treatment of resistant ophthalmomycosis, in particular keratomycosis, after limited clinical trials in various variations.